2021
DOI: 10.3390/d13060238
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Trade in a Songbird That Is Extinct in the Wild

Abstract: Indonesia is at the epicenter of the Asian Songbird Crisis, i.e., the recognition that the cage bird trade has a devastating impact on numerous imperiled bird species in Asia. The Javan pied starling Gracupica jalla, only in the last five years recognized as distinct from the pied starlings of mainland Southeast Asia, has been declared extinct the wild in 2021. Up until the 1980s, it used to be one of the most common open countryside birds on the islands of Java and Bali, Indonesia. From the early 2000s onward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Tackling the illegal trade in non-protected and less charismatic animals such as Java's hill partridges is never going to be easy. 1,2,[5][6][7][8][9] With substantial monetary gains to be made from the illegal wildlife trade, generally low risks of detection and prosecution, and with enforcement efforts spread out over vast geographic areas, this is a daunting task. The many postings of hill partridges on three of the four online platforms as well as on Facebook are in clear violation of their terms and policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tackling the illegal trade in non-protected and less charismatic animals such as Java's hill partridges is never going to be easy. 1,2,[5][6][7][8][9] With substantial monetary gains to be made from the illegal wildlife trade, generally low risks of detection and prosecution, and with enforcement efforts spread out over vast geographic areas, this is a daunting task. The many postings of hill partridges on three of the four online platforms as well as on Facebook are in clear violation of their terms and policies.…”
Section: Discussionmentioning
confidence: 99%
“…Chng et al 6 ), monitoring of birds offered for sale in markets in one city, either over the course of several months 2 or several years, 7 or monitoring of single species for sale in bird markets over a larger geographical area over several years. 8 Declines of wild bird populations due to overharvesting may be noticeable in the trade (smaller numbers, fewer markets, higher prices, etc.) after decades rather than years.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, a central player in the Asian bird trade [14], is a crucial geographic area of study due to its diverse bird species traded for various human uses, from entertainment to traditional medicine [15,16]. The trade of birds for human entertainment is the major factor driving an increasing number of Asian species to extinction, with species desired for their singing abilities and/or other attractive attributes, such as their colorful plumage [14].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this trade in birds, and the research into its scope, scale, and conservation implications, has been centered around songbirds (Passeriformes), which are acknowledged to be under immense pressure from both domestic and regional trade, to a level that the current situation has been described as the 'Asian songbird crisis' [14,17]. An increasing awareness of this crisis and the need to better understand trade dynamics have prompted a series of large-scale market surveys across the Southeast Asian region, and most notably in Indonesia [14][15][16][17][18]. These studies, many of which involve full inventories of all bird taxa found in trade, have revealed that songbirds are just one of many orders of birds that are traded in the Southeast Asian bird markets [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In order to fulfill the needs of bird demand, traders always try to provide birds to buyers. The upwards trend in catching and selling bird species threatens bird population in Asia, with Indonesia as the epicenter of songbird crisis (Nijman et al 2021b). This fact is reasonable as data acquired from Nijman et al (2019) showed approximately tens of thousands of birds caught from the wild were sold in the markets in Java Island each day.…”
Section: Introductionmentioning
confidence: 99%